PENGELOLAAN ZAKAT PERSPEKTIF HUKUM ISLAM KONTEMPORER - Abdain, Abdain (DIKTUM: Jurnal Syariah dan Hukum, 2015)
Islam provides guidance to its adherents who are facing the problem of social inequality by placing tithe as one of the main pillars of Islamic establishment, especially in anticipation of the growth of dynamics and economic equality in society. As a source of funds, tithe is potential to be used as capital for the construction of the Muslims, and it will be very effective in anticipating the social gap in the community. Classical scholars, generally categorize the subject to tithe is cattle, gold, silver, merchandise, property excavation, and agricultural products. Today, contemporary ijtihad, one of which is represented by the book of Yusuf Qardawi, specify wealth that is subject to tithe, as many models and forms of wealth that was born from the increasing of complexity of economic activities. Yusuf Qardawi divide tithe into nine categories: tithe of cattle, tithe of gold and silver which includes money, tithe of trade, tithe of agricultural output includes farmland, tithe of honey and animal production, tithe of minerals and marine products, tithe of plant investment, buildings and others, tithe of livelihood, tithe of services and professions, and tithe stocks and bonds.